Biallelic PMS2 Mutation and Heterozygous DICER1 Mutation Presenting as Constitutional Mismatch Repair Deficiency With Corpus Callosum Agenesis: Case Report and Review of Literature. Issue 7 (October 2017) - Cheyuo, Cletus; Radwan, Walid; Ahn, Janice; Gyure, Kymberly; Qaiser, Rabia; Tomboc, Patrick
Abstract : Constitutional mismatch repair deficiency syndrome is a cancer predisposition syndrome caused by autosomal recessive biallelic (homozygous) germline mutations in the mismatch repair genes ( MLH1, MSH2, MSH6, and PMS2 ). The clinical spectrum includes neoplastic and non-neoplastic manifestations. We present the case of a 7-year-old boy who presented with T-lymphoblastic lymphoma and glioblastoma, together with non-neoplastic manifestations including corpus callosum agenesis, arachnoid cyst, developmental venous anomaly, and hydrocephalus. Gene mutation analysis revealed pathogenic biallelic mutations of PMS2 and heterozygous DICER1 variant predicted to be pathogenic. This report is the first to allude to a possible interaction of the mismatch repair system with DICER1 to cause corpus callosum agenesis.